The Function of Organic Additives in Enhancing the Q-values for Peat Pellet Biofuel - Nor Zakiah Nor Hashim; Zaidi Embong (ASM Science Journal, 2021)
In Malaysia, peat make up for around 7.5 % of the entire land area. The positive effect of the vast wet organic compounds accumulates over a long time has stored high content of soil’s carbon which are highly useful as fuel and biomass energy generation. Thus, this study gives an outline of peat pellet as potential biofuel energy.  The peat pellets were soaked into several kinds of flammable additives such as petrol, kerosene and diesel. The percentages of 69.41 % of carbon, 28.73% of oxygen and 0.97% of silicon were obtained using Energy Dispersive X-ray (EDX). The Fourier-Transformed Infrared (FTIR)- Attenuated Total Reflectance (ATR) Spectroscopy was used to identify the sample.  From the spectra, it reveals that most of the additives contribute mainly functional groups with hydroxyl, alcohol and phenol groups were found leading to higher boiling and melting points. The heat combustion properties of peat pellets were evaluated using a calorimeter technique by boiling off 50 ml and 100 ml of water. The pellet with diesel has the highest Q-values and combustion rate due to larger number of carbons in rigid molecular structure. The high amount of unique chemical compound found naturally in diesel known as cetane, ignites effortlessly when heated gives diesel additional advantages in shorter ignition delays as well as longer duration of combustion.